(untitled) (The Macau Ricci Institute Journal, 2018)
Confucian education is best captured by the programme described in the Great Learning. Education is presented first as the process of self-cultivation for the sake of developing virtuous character. Self-cultivation then allows for virtue to be cultivated in the familial, social and international dimensions. My central thesis is that Confucianism can serve as a universal framework of educating people for the common good in its promotion of personal cultivation for the sake of human progress. On this account the common good specifically refers to the social order accomplished by the virtuous behaviour found in the members of society. In this paper I argue that the Confucian notion of “lesser learning” sheds light on the concept of general education and the notion of “greater learning” improves our understanding of liberal education. Under this analysis the necessity of general education is assured although its importance should not be overly exaggerated. Furthermore, the objectives of liberal education deserve greater emphasis due to their historical importance and enduring relevance to promoting the common good of universal humanity.